Violence and instrumentalism. On the margins of Tyson Lewis's Walter Benjamin's Antifascist Education. Issue 3 (3rd July 2022) - Sosnowska, Paulina
ABSTRACT: My response to Tyson Lewis's book concentrates on two themes, seemingly peripheral to the book's explicit content: the pertinent question of (educational) violence and the related problem of instrumentalism. I try to tackle both of them by outlining the dispute between Walter Benjamin and Carl Schmitt. The choice of Schmitt as the background for these peripheral commentaries is not accidental. The premise of Lewis's book is that there is a link between fascism and 21st century populism and authoritarianism (in the US, France, and Germany, but – as I would argue – much more prevalent in Hungary and Poland). The European version is, if not intellectually connected, then at least somehow coincident with the renaissance of the thought of the German jurist of the Weimar and Nazi era. Benjamin's antifascist potential depends also on his power of de-potentializing Schmitt's political theology, concepts of sovereignty and state of exception.